Pola Konsumsi Masyarakat Kota Samarinda di Era Cashless Society - Wahidatul Hidayah; Ratna Fitri Astuti; Reza Reza; Sudarman Sudarman; Noor Ellyawati (Jayapangus Press, 2026)
Consumption patterns are changing with the development of the cashless society era, which is characterized by the ease of digital transactions and the increasing use of online platforms in daily economic activities. In Samarinda, this convenience has the potential to influence how individuals manage expenses and determine consumption priorities. This study aims to analyze the consumption patterns of Samarinda residents in the cashless society era and identify the most dominant indicators in shaping consumption behavior. The study used a quantitative approach with a descriptive design. The sample consisted of 100 adult respondents aged 19–59 years old, determined using the Slovin formula with the sampling technique being accidental sampling. Data were collected through a Likert scale questionnaire and analyzed using descriptive statistics with the calculation of averages and percentages of data. The results of the study, which measured consumption expenditure indicators, changes in consumption over time, the intensity of use of goods and services, and purchasing behavior, showed that in general, the consumption patterns of Samarinda residents were in the very good category with 63% of respondents, followed by the good category with 36%, and only a small portion were in the very bad category. Community expenditure was dominated by basic needs and followed by savings habits. In addition, people tend to shop through online platforms with marketplaces as the main choice. In the purchasing process, people prioritize product quality and authenticity over other factors. These results indicate that Samarinda residents are still able to manage their consumption rationally and purposefully despite the ease of digital transactions. The most dominant indicator of consumption patterns is purchasing behavior, which reflects people's ability to control spending and make informed decisions.